Safety and efficacy of a tincture derived from Verbascum thapsus L. when used as a sensory additive in feed for all animal species. (6th December 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of a tincture from Verbascum thapsus L. (great mullein tincture) when used as a sensory feed additive for all animal species. The product is a water/ethanol (■■■■■) solution, with a dry matter content of approximately 2.8%. The product contains on average 0.216% polyphenols and 0.093% flavonoids. Since 82% of the dry matter fraction of the additive remains uncharacterised, the FEEDAP Panel cannot identify a safe level for the use of the additive for all animal species. Considering the uncertainty in the composition of the additive, and in the absence of information on the toxicological properties of the tincture, the FEEDAP Panel is unable to conclude on the safety for the consumers following the use of the tincture as flavouring in animal feed. No specific data were provided by the applicant regarding the safety of the additive for users. In the absence of data, no conclusions can be drawn on the additive's potential to be a dermal/eye irritant or a skin sensitiser. V. thapsus L. is native to Europe. Consequently, the use of a tincture derived from the plant at the maximum proposed dose is not considered to be a risk for the environment. Since the major components of the additive are recognised to provide flavour in food and its function in feed would be essentially the same, no demonstration of efficacy is considered necessary.